Designing uncertain optimization schemes for the economic assessment of stock energy-efficiency measures. Issue 1 (2nd January 2017) - Das, Payel; Van Gelder, Liesje; Janssen, Hans; Roels, Staf
Abstract : There are a myriad of options when it comes to designing an uncertain optimization scheme. This work explores the impacts of several of these options using a case-study retrofitting of Swedish attics developed during the Annex 55 project of the International Energy Agency Energy Buildings and Community programme. We find that not considering maintenance costs, increments in energy costs with time, and discount rates in the economic criterion can impact the derived optimal design option. However, for our case study no difference was found between criteria that examined absolute returns, fractional returns, and annulized returns, despite emphasizing different aspects of the investment. If multiple moments of the economic criterion distribution are combined with weights to create a single objective function then several weights should be explored. Alternatively a single moment could be sought, such as the probability that the economic criterion is negative as a sufficient single objective, avoiding having to choose a weight. A hybrid genetic algorithm may offer a more efficient method of determining the optimal design option but a multi-layered sampling scheme offers more flexibility regarding subsequent analysis.